Nivel de logro de la comprensión de textos escritos argumentativos en los estudiantes del VII ciclo de educación secundaria de la Institución Educativa P.I.P/S.M. N° 60087 Lucille Gagne Pellerín, Napo 2023 - Manihuari Pisco, Ingri (2025)
The objective was to describe the level of achievement of the comprehension of argumentative written texts in students of the Third, Fourth and Fifth grade of secondary school of the Educational Institution P.I. P/S.M. N° 60087 “Lucille Gagne Pellerin of the district of Santa Clotilde, river – Napo. For this, the quantitative approach was used with a descriptive non-experimental cross sectional design. A sample of 240 students from the VII cycle of the I.E. P.I.P/S.M. N° 60087 “Lucille Gagne Pellerin”, Napo, 2023. The technique used was the survey and the instrument was the questionnaire. The statistical package SPSS version 27 was used to process the information. The results indicate that 68.3% of students are at the Beginning The study concludes that there is a very low level of understanding of argumentative written texts, a situation that shows that they have not developed optimal levels that guarantee them the understanding of life's problems, as well as developing critical thinking, creativity and problem solving.